Pengaruh Motivasi Terhadap Kinerja Kerja Karyawan PT. Telkom Indonesia Tbk Cabang Malang - Bambang Ragil (Jurnal Ekonomi dan Manajemen, 2019)
The objectives of this study are: i) To determine the effect of motivation (External and Internal) on Employee Work Performance; ii) To find out which motivation (External and Internal) is dominantly influential on improving employee work performance. This study uses a survey system by distributing questionnaires to predetermined respondents. This type of research uses observations with Cross Sectional design, which is to determine the relationship between motivational variables and performance. The population of this study amounted to 65 employees working in Telkom Tbk Malang. The sample in this study was all employees totaling 65 people or samples. The statistical analysis used in this study is the path analysis approach with the help of SPSS. The results of this study indicate that: From the results of the description analysis that if there is an increase in external and internal motivation, the work performance of employees will also increase. From the test of the dominant variable where the dominant external motivation is found to have an effect on improving employee work performance.